Schrödinger Operators on a Zigzag Supergraphene-Based Carbon Nanotube (Communications in Computational Physics, 2018)
Throughout this paper, we study the spectrum of a periodic Schrödingeroperator on a zigzag super carbon nanotube, which is a generalization of the zigzagcarbon nanotube. We prove that its absolutely continuous spectrum has the band structure.Moreover, we show that its eigenvalues with infinite multiplicities consisting ofthe Dirichlet eigenvalues and points embedded in the spectral band for some correspondingHill operator. We also give the asymptotics for the spectral band edges.